Pitting-corrosion on internal wall of tee-pipe joined with main-pipe for seawater tank-washing system of a tanker. (October 2019) - Yu, Hai-xuan; Xu, Xiao-lei; Yu, Zhi-wei
Abstract: Pitting corrosion occurred on a tee-pipe joined to main-pipes for seawater tank-washing system of a tanker after sea-trial of only one month. The tee-pipe was made of AISI 316 L stainless steel and the internal wall was required to be passivated. On-site inspection indicated that corrosion-pits were presented in the specified areas on the internal wall of bottom of tee-pipe which can easily retain seawater, and mostly concentrated on the outsides of weld ends. The morphology features of corrosion-pits and the high concentration chlorine in corrosion products located inside the corrosion-pits and on the internal wall of tee-pipe in vicinity of pit-clusters suggested that the damage was due to pitting-corrosion in chloride-containing seawater. Visual and SEM observations revealed that grinding marks occurred on the internal wall of the ends of tee-pipe close to the weld. Grinding operation on the ends of tee-pipe before welding destroyed the integrity of passive film, even locally removed off the passive film. When the affected area was exposed to the seawater containing chloride, the defective areas on passive film could promote the localized corrosion, pitting corrosion. Furthermore, the area with imperfect passive film acted as an anode, whereas the area with perfect passive film acted as a cathode leading to preferential attack at the ground region. The rate of localized attack was very fast in a system with a large cathode and a small anode to lead to pitting failure after a short service time of one month. Highlights: Pitting occurred on the specified regions of internal wall of tee-pipe. Grinding or scratching marks were found on the internal wall with clustered pits. Grinding operating before welding destroyed the passive film on the internal wall.